Factors of employability skills of engineering graduates: An analytical study using Friedman Test Multiple Regression - Roja Rani, V; Kishore Babu, M (International Journal of Engineering and Technology, 2018)
Employability skills and placement rate becomes the buzz words to bench mark for the quality of engineering education among the technical institutes in the country. The gap between pass out ratio and placement ratio among the engineering graduates is alarming and indicating the poor levels of skill set of the engineers. The reasons for the same are many and multifold. The present paper is focused on studying the role of personal factors, life skills factors, teaching and learning factors, and evaluation systems and improvement practices environment in the employability of the engineering graduates from Hyderabad city. For the purpose of the study, selected students from the engineering colleges in the city are drawn as sample using judgment sample method. The study is descriptive and exploratory in nature. The sample size for the study is fixed at 600 and the final analysis is done with 512 samples. The data required for the study is collected through a pretested structured questionnaire. All the students are from eighth semester and appearing for placements. Some of the students are already placed and waiting to complete the course. The combination of the experiences in the interviews and the skill gaps observed in the self assessment is presented.The study results reveal that, life skill factors, teaching learning and evaluation systems are highly important in employability skills of the engineering graduates. The relationship between the employability and the selected variables are highly significant at 1% level of significance. A structured practical sessions and application oriented training along with practical sessions and strict evaluation systems along with options for improvement can help the students to realize and learn the required skills and there by improved level of employability among the engineering graduates in the sample. Further, it indicates the need for revamping the old pedagogy and adoption of new ICT and CTT in teaching learning processes can help in resolving the issue at the earliest possible time. The role of a teacher can never give up in training and molding the young graduates of any selected field of study. The teacher issues Â in this sector needs a special care and concern to get the improved level of professional deliverables and service quality among the technical institutions in the field.Â Â